Perencanaan Pengumpulan Data sebagai Identifikasi Kebutuhan Pelatihan Lembaga Pelatihan - Darmawan, Dadan; Sudrajat, Indra; Maulana, M. Kahfi Zaeni; Febriyanto, Budi (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2021)
Needs can be a desire to improve current performance or to correct shortcomings. Disadvantages are performance that does not meet current standards. This meansthat there are ways that are determined in carrying out a task and the differenceis creating a problem. The process of identifying needs helps trainers and peoplerequesting training to determine training needs or lack of performance.Identification can be formal (using survey and interview techniques) or informal(asking questions about those involved). data collection in the identification oftraining needs at training institutions in the city of Bandung, namely: Planningdata collection in the identification of training needs at training institutions inthe city of Bandung, which is compiled based on data or information to beobtained related to training programs that meet the target needs. So to get thedata, each institution has different data collection techniques. The choice of thetechnique is determined by several factors including the depth and clarity of thedata to be obtained, the target of identifying needs that includes the number andlocation of the target, and the number of data collectors.